A key to species of the genus Hylaeus (Hymenoptera: Colletidae) from mainland of China with descriptions of new species and new records - Chen, Xuan; Xu, Huanli (Zootaxa, 2009)
The subgenus Hylaeus (Dentigera) Popov is recorded from East Asia for the first time based on a new species, Hylaeus luna sp. nov., from Hubei, China, herein described. Hylaeus concinnus Cockerell, H. dolichocephalus Morawitz, H. niger Bridwell and H. paulus Bridwell are recorded from China, as well as H. dorni Dathe whose female is described. A key to all species of Hylaeus known to occur in mainland China is presented.